Literature Review of Case Reports Regarding NLW Thoracic Impacts - Andrei, A.; Robbe, C.; Papy, A.; de Schoutheete, J. C. (Human factors and mechanical engineering for defense and safety, 2023)
During the last decades, there has been an increase in the development and use of kinetic energy non-lethal projectiles, mainly because of their ability to neutralise without inflicting serious injuries. Even though these are intended to temporarily incapacitate individuals, it is often encountered that kinetic impact projectiles can cause penetration, severe injuries, permanent disabilities and even mortality. The injury level is highly related to the shot distance and the body region that is impacted. Because the thoracic region is the dominant impact region and because it hosts vital organs, it is considered to be one of the most sensitive areas of the human body. Therefore, all injuries to the chest should be regarded as potentially life threatening. The objective of this study is to review case reports and case studies of kinetic energy projectiles’ impacts on the thoracic region available in open literature. The ballistic and operational conditions and also medical outcome of each case are described. The study includes penetrative and non-penetrative impacts of different kinds of projectiles (rubber bullet, plastic bullet, bean bag, flashball, FN303) in order to be able to comprehend the injury potential of these projectiles and to provide an insight into real shooting conditions. The difficulties and limitations of the literature study are presented.